Connecting Sub-Saharan Africa : A World Bank Group Strategy for Information and Communication Technology Sector Development - Guislain, Pierre; Ampah, Mavis A.; Besançon, Laurent; Niang, Cécile; Sérot, Alexandre (Washington, DC: World Bank, 2012)
The strategy builds on the earlier reform agenda in the sector by leveraging the achievements to date of Sub-Saharan African countries to advance the essential goal of increasing the continent's connectivity. It provides strategies for developing and enhancing the capacity of Africa's information and communication technology sector (ICT) institutions-including regulators, ministries, and regional bodies-to lead the development of an interconnected region and implement sustainable regional strategies for integration and knowledge sharing. Of particular concern is the ability to bring rural areas into the national, regional, and global economies, thus creating new opportunities for the world's poorest citizens.